Between Hope and Reality: Problems of Learning Arabic in Class 5-S KMI Pondok Modern Darussalam Gontor 2023-2024 Academic Year - Agus Yasin; Muhammad Kautsar Ramadhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
When learning Arabic, students and teachers are often faced with existing problems. Gontor is no exception, which in fact is an Islamic boarding school-based educational institution that upholds Arabic language learning. Broadly speaking, there are two problems with learning Arabic, namely: Linguistic and Non-Linguistic. Among the linguistic problems faced by KMI Gontor class 5-S students are: (a) the students are less proficient in capturing and digesting the material presented by the teacher, where the language of instruction for these materials is Arabic, (b) the students are less proficient in reading bald Arabic texts (Arabic texts without harokat), (c) students are less proficient in the kitabah (writing). Even the writing they write themselves sometimes they can't read, (d) the students' nahwu and Sharaf abilities are very poor. Meanwhile, non-linguistic problems faced by class 5-S students include: (a) students' lack of interest and motivation in studying Arabic so that their abilities do not develop and tend to be very poor compared to their peers, (b) some teachers are less proficient in delivering the material. Actively, tend to only transfer knowledge, not provide enthusiasm and constructive impressions to students during learning activities.